2018
DOI: 10.1002/chem.201800930
|View full text |Cite
|
Sign up to set email alerts
|

Detecting Proton Transfer in CO2 Species Chemisorbed on Amine‐Modified Mesoporous Silicas by Using 13C NMR Chemical Shift Anisotropy and Smart Control of Amine Surface Density

Abstract: The wealth of site-selective structural information on CO speciation, obtained by spectroscopic techniques, is often hampered by the lack of easy-to-control synthetic routes. Herein, an alternative experimental protocol that relies on the high sensitivity of C chemical shift anisotropy (CSA) tensors to proton transfer, is presented to unambiguously distinguish between ionic/charged and neutral CO species, formed upon adsorption of CO in amine-modified porous materials. Control of the surface amine spacing was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
62
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(69 citation statements)
references
References 42 publications
7
62
0
Order By: Relevance
“…Indeed, recent work on amine-functionalized silicas has shown that the use of the anisotropy of the 13 C chemical shift (rather than simply isotropic chemical shifts) can enable identification of neutral versus charged chemisorption products. 52 Overall, these studies demonstrate that 1 H, 13 C, and 15 N NMR experiments, combined with DFT calculations, provide far more reliable structural assignments than 1D NMR experiments and calculations on a single nucleus. Figure 8) with key 1 H - 13 C HETCOR correlations indicated by blue arrows and labels A-E. Gas dosing times were >13 hours in all cases, and care was taken to avoid air exposure between sample activation and gas dosing, as water vapor has a large effect on the chemisorption mechanism (see below).…”
Section: Resultsmentioning
confidence: 71%
“…Indeed, recent work on amine-functionalized silicas has shown that the use of the anisotropy of the 13 C chemical shift (rather than simply isotropic chemical shifts) can enable identification of neutral versus charged chemisorption products. 52 Overall, these studies demonstrate that 1 H, 13 C, and 15 N NMR experiments, combined with DFT calculations, provide far more reliable structural assignments than 1D NMR experiments and calculations on a single nucleus. Figure 8) with key 1 H - 13 C HETCOR correlations indicated by blue arrows and labels A-E. Gas dosing times were >13 hours in all cases, and care was taken to avoid air exposure between sample activation and gas dosing, as water vapor has a large effect on the chemisorption mechanism (see below).…”
Section: Resultsmentioning
confidence: 71%
“…As for solid-supported amines, because of the limited mobility of amine groups, it is surmised that water catalytic assistance becomes prominent for a low amine surface density, leading to carbamic acid or hydronium carbamate (CO 2 /N = 1), often stabilized by hydrogen bonding. 15 , 19 , 24 , 25 Notice that hydroxyl groups may play the same assisting role as water vapor. 29 This is consistent with experimental evidence as the enhancement of amine efficiency under humid conditions was found to be most pronounced for low amine surface coverage.…”
Section: Resultsmentioning
confidence: 99%
“… 26 Furthermore, the nature of the chemical species formed and the amine efficiency, that is, the CO 2 /N ratio, were found to depend on the surface density of amine groups. 16 , 19 , 24 , 27 Although the formation of alkylammonium carbamate is often dominating under dry conditions, Cendak et al 19 found that at low surface density, supported amines give rise mainly to carbamic acid, whereas at high density, the formation of alkylammonium carbamate prevails. Carbamic acid was also demonstrated to occur in the absence of moisture, on primary amine-bearing metal–organic frameworks, 21 or other hydrophobic media.…”
Section: Introductionmentioning
confidence: 99%
“…Traditionally, Fourier-transform infrared (FTIR) spectroscopy has been used as the leading tool in species identification. More recently, nuclear magnetic resonance (NMR) has emerged as a powerful alternative 39 , able to discriminate not only between different species 25, 27-28, 30, 34-35, 40-46 , but also different conformations of the same species 32,47 . These studies use mainly 13 C NMR, in order to detect CO2-amine adducts.…”
Section: Introductionmentioning
confidence: 99%
“…The silica surface model was intentionally faded out to better emphasize the propylamine chains. Resonance C is associated with model 1 from Figure 1, resonance B with 3, resonance B' with 4, resonance A with 5 and resonance A' withMany authors, including us, have tried to investigate how amine loading impacts the nature of CO2 species formed in silica-based materials29,47,[62][63] ; however, computational studies modelling CO2 structures in conditions of high-and low-amine loadings are extremely scarce42 . Whether CO2 species are isolated or establishing hydrogen bonds with neighbouring amines, with or without the involvement of hydrogen bonded silanol groups, is still very debatable and very difficult to verify through experimental evidence.…”
mentioning
confidence: 99%